PERAN GURU PIAUD DALAM MENGEMBANGKAN KETERAMPILAN MEMBACA HURUF HIJAIYAH PADA ANAK USIA DINI - Nurkaila Nurkaila; Epa Epa; Alam tarlam (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Learning the hijaiyah letters in early childhood is a crucial stage in establishing the foundation for Quranic reading skills. Early Childhood Islamic Education (PIAUD) teachers play a strategic role because the educational process in this age group requires an approach that aligns with the child's developmental characteristics. This article aims to explain the role of PIAUD teachers in developing hijaiyah reading skills, including appropriate learning methods, media that can be used, and supporting and inhibiting factors encountered in the field. Theoretical studies and discussion indicate that the teacher's role includes planner, facilitator, guide, motivator, and evaluator. The use of play-based approaches, multisensory methods, a religious learning environment, and collaboration between schools and parents are key to the effectiveness of hijaiyah learning in PIAUD. This article is expected to serve as a reference for teachers, PIAUD students, and educational institutions in improving the quality of Islamic learning in early childhood.